Social Control as Fraud Prevention Effort in State Audit Institutions - Suci Amelia Harlen; Anggi Aulina Harahap (Association of Certified Fraud Examiners Indonesia Chapter, 2022)
Fraud is deviation by abusing work that results in losses for personal gain. The focus of this study is to analyze the relationship between social control and fraud prevention efforts at state audit institutions. The research method uses a literature study that is representative and relevant to the object of research. Auditors are vulnerable to fraudulent acts in their daily work, such as corruption, gratuities or regulatory authorities. The problem is how strong the auditor’s social control is in the form of internal and external self-defense so as not to fall into fraudulent actions. This study aims to expand the prevention of fraud on auditors with detention.